665 MODELING OF PRIMARY DISTILLATION PROCESS OF VEGETABLE OIL MIСCELLA - Ikromova, Yulduzxon; Ikromov , Farruxbek; Hamdamov, Anvar; Xudayberdiyev, Absalom (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article describes the behavior of the water vapor-liquid system and the basics of building a mathematical model of the process during the initial distillation of cottonseed oil miccella. By building a mathematical model of the process, the selection of optimal process parameters and the acceleration of the heat exchange process in the water-vapor-liquid system were studied. Automation of the distillation process ensures control of the water vapor-finished product concentration. Coupling the studied process through mathematical expressions helps in more precise analysis of the cottonseed oil miccella distillation process. Based on the main goal of the research work, mathematical modeling of the final miccella distillation process and optimization of technological schemes, developed models and algorithms for their solution are designed to perform the functions of calculating individual elements of the scheme and therefore its components are a general algorithm for synthesizing an effective technological scheme for the separation of target products. The division of a complex system into separate functional subsystems allows for the most rational detailed study of the technological process and the most effective identification of the object based on a complete mathematical description of the object, obtaining a reliable, realistic idea. Methods of carrying out the process in stable and unstable conditions help to solve optimization issues at the level of technological complexes as modes of its occurrence and chemical-technological systems.